Effects of FSGS-associated mutations on the stability and function of myosin-1 in fission yeast - Jing Bi; Robert T. Carroll; Michael L. James; Jessica L. Ouderkirk; Mira Krendel; Vladimir Sirotkin (The Company of Biologists, 2015)
Point mutations in the human MYO1E gene, encoding class I myosin Myo1e, are associated with focal segmental glomerulosclerosis (FSGS), a primary kidney disorder that leads to end-stage kidney disease. In this study, we used a simple model organism, fission yeast Schizosaccharomyces pombe, to test the effects of FSGS-associated mutations on myosin activity. Fission yeast has only one class I myosin, Myo1, which is involved in actin patch assembly at the sites of endocytosis. The amino acid residues mutated in individuals with FSGS are conserved between human Myo1e and yeast Myo1, which allowed us to introduce equivalent mutations into yeast myosin and use the resulting mutant strains for functional analysis. Yeast strains expressing mutant Myo1 exhibited defects in growth and endocytosis similar to those observed in the myo1 deletion strain. These mutations also disrupted Myo1 localization to endocytic actin patches and resulted in mis-localization of Myo1 to eisosomes, linear membrane microdomains found in yeast cells. Although both mutants examined in this study exhibited loss of function, one of these mutants was also characterized by the decreased protein stability. Thus, using the yeast model system, we were able to determine that the kidney-disease-associated mutations impair myosin functional activity and have differential effects on protein stability.